Reduction of harvest losses in mango (Mangifera indica L.) fruit using improved harvesting methods - Elkashif, Mohamed; Adam, A.M; Elamin, O.M (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
An experiment was conducted in a private orchard, located along the Blue Nile bank at Hantoub, Gezira State during the seasons of 2007 and 2008, to investigate the effect of improved harvesting methods on reducing physical injury during harvesting of mango fruits of selected cultivars viz. Kitchener (Baladi), Alphonso, Timour, Abu Samaka and Gulbeltour. The experimental design was a split plot with three replications. Cultivars were assigned to the main plots and harvesting methods to the subplots. The harvesting methods consisted of a ladder, a modified picking pole (MPP), a straw mattress (SM) and the traditional picking pole (control). The ladder harvesting method resulted in the lowest percentage (4.4%) of physical injury followed by the modified picking pole (16.0%) and the straw mattress (29.5%), while the traditional picking pole resulted in the highest percentage (53.1%) of physical injury. The cultivar Gulbeltour and Abu Samaka showed the highest percentage of physical injury, while Timour showed the lowest. Both the ladder and the modified picking pole harvesting methods took the longest time (44 minutes) to harvest one hundred mango fruits followed by the straw mattress (19 minutes) and then the traditional method (10 minutes). The cultivars Alphonse, Kitchener and Timour required less time to harvest one hundred fruits, while Gulbeltour and Abu Samaka required more time.      أجريت هذه التجربة في مزرعة خاصة للفاكهة على شاطئ النيل الأزرق بحنتوب ، ولاية الجزيرة في موسمي (2007 و2008) بغرض استخدام بعض طرق الحصاد المحسنة لتقليل الأضرار الميكانيكية التي تحدث لثمار المانجو أثناء الحصاد. استخدم في ذلك نظام تصميم القطع المنشقة بثلاثة مكررات، حيث وزعت الأصناف على القطع الرئيسية وطرق الحصاد على القطع المنشقة. استخدمت خمسة أصناف من المانجو وهي (كتشنر، الفونس، تيمور، أبو سمكة وقلب التور). تم حصادها باستخدام طرق الحصاد الآتية: وهي السلم، الجبادة المحسنة ذات الآلة القاطعة وكيس من القماش و فرشة من الخيش مليئة بأوراق المانجو الجافة بالإضافة إلى الطريقة التقليدية (الجبادة). أوضحت النتائج أن السلم أعطى أفضل نتيجة (4.4%) في تقليل نسبة إصابة ثمار المانجو ثم يأتي بعده الجبادة المحسنة (16.0%) وثم الفرشة (29.5%). بينما أعطت الطريقة التقليدية أكبر نسبة إصابة لثمار المانجو (53.1%). الأصناف قلب التور وأبو سمكة أعطت أعلى نسبة إصابة للثمار بينما الصنف تيمور أعطى أقل نسبة إصابة. أما بالنسبة للزمن المستغرق في الحصاد لكل طريقة ، نجد أن الحصاد بالسلم استغرق أطول زمن (45 دقيقة)، تلاه الجبادة المحسنة (44 دقيقة) ثم الفرشة (19 دقيقة) بينما استغرقت الطريقة التقليدية أقل زمن (10 دقائق) في حصاد المائة ثمرة من المانجو. الأصناف الفونس وكتشنر وتيمور استغرقت أقل زمن لحصاد 100 ثمرة بينما استغرقت الأصناف قلب التور وأبو سمكة زمناً أطول لحصاد نفس العدد من الثمار.